Evaluation of antimicrobial activity and phytochemical qualitative analysis of Ephedra foliata Boiss. ex C.A. Mey. - Singh Mahabir; Rajput Minakshi; Yadav Kuldeep; Singh Narender (Herba Polonica, 2022)
Introduction: Ephedra foliata Boiss. ex C.A. Mey of the Ephedraceae family is an evergreen shrub distributed throughout North Africa and Southwest Asia. It has been a characteristic source of alkaloids like ephedrine, pseudoephedrine and other related mixes, which are of great importance for their biological and pharmacological potential.